Biogenic Synthesis of Silver Nanoparticles (AgNPs) using Solanum indicum Linn. - Alhag, Sadeq Khalid; Ghramah, Hamed Ali; Al-keridis, Lamya Ahmed; Al-Mekhlafi, Fahd Abdu; Ibrahim, Essam Hassan; Khan, Khalid Ali (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Synthesis of silver nanoparticles (AgNPs) using green plants is important for biocompatibility, reduced hazards, green policy and eco-friendliness. Materials and Methods: In this study, a leaf extract of Solanum indicum and associated AgNPs were used to examine larvicidal properties and other biological activities. AgNP forms were characterized with scanning electron- microscopy (SEM), Fourier Transform Infrared Radiation spectroscopy (FTIR) and UV-vis spectra. Larvicidal activity was assessed with Culex pipiens larvae using the World Health Organization method. Antibacterial potential of S. indicum leaf extract and AgNPs were evaluated with a well diffusion assay. In vitro impacts of S. indicum extract and AgNPs were studied using spleen cell propagation. Results: S. indicum ethanol extract and associated AgNPs show larvicidal activity against 4th instar of Cx. pipiens. Synthesized AgNPs were more toxic, with lower lethal concentration values, (LC50 = 47.181 ppm; LC90 = 243.776ppm) compared to plant extract (LC50 = 131.448 ppm; LC90 = 4397.528 ppm) after a twenty-four hour of exposure. Synthesized AgNPs also show significant impact Staphylococcus aureus, Proteus mirabilis, Escherichia coli and Shigella flexneri. Cytotoxic effects were demonstrated for S. indicum extract and AgNPs on normal spleen cells. The extract and associated AgNPs were also safe for red blood cells (RBCs) and failed to cause substantial elevation in serum liver enzymes. Conclusion: Leaf extracts of S. indicum and associated AgNPs may be efficient and eco-friendly for control of Cx. pipiens. Their antibacterial activity may be useful if care is taken to prevent cytotoxic effects.
Keywords: Cytotoxic effect; Culex pipiens; Silver Nanoparticles; Antibacterial; Larvicidal; Solanum indicum